The Code of Virginia: With the Declaration of Independence and the Constitution of the United States, and the Constitution of Virginia 377, tit. 52, ch. 184, § 3780 (1887) - (:unkn) unknown (General Publisher, 1887)
Prohibited the carrying of a concealed pistol, dirk, Bowie knife, razor, slungshot, or any weapon of the like kind. Punishable by fine of $20-100 and forfeiture of the weapon.
--
Keywords: CARRY - CONCEALED